Pengaruh Kombinasi Aromaterapi Mawar Dan Edukasi Terhadap Tingkat Kecemasan Pada Pasien Pre Operasi Pembedahan Elektif Di RSUD dr. Soedomo Trenggalek - Marsaid; Deliya , Deliev; Wiyono, Joko; Ciptaningtyas, Maria Diah (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: To determine the effect of a combination of rose aromatherapy and education on anxiety levels in elective surgical preoperative patients at RSUD Dr. Soedomo Trenggalek. Methods: This article is quantitative with a quasi-experimental research design (two group pretest-posttest design). The sample in the study were 32 respondents who experienced anxiety before elective surgery using purposive sampling technique. The research instrument used the APAIS anxiety scale. The main data were analyzed using the Wilcoxon test. Results: The results showed that the average anxiety score before the intervention was 13.88 (moderate anxiety), while the average anxiety score after the intervention was 8.88 (mild anxiety) and the results obtained were ρ value 0.000 (ρ value 0.000 < α 0.05), meaning that there is a combined effect of rose aromatherapy and education on anxiety levels in preoperative elective surgical patients. Conclusion: So that the combination of rose aromatherapy and education can be used to reduce anxiety levels in elective surgical preoperative patients.